Effect of 2D and 3D Culture Microenvironments on Mesenchymal Stem Cell-Derived Extracellular Vesicles Potencies - Kusuma, Gina D.; Li, Anqi; Zhu, Dandan; McDonald, Hannah; Inocencio, Ishmael M.; Chambers, Daniel C.; Sinclair, Kenneth; Fang, Haoyun; Greening, David W.; Frith, Jessica E.; Lim, Rebecca (Frontiers in Cell and Developmental Biology, 2022)
Therapeutic benefits of mesenchymal stem cells (MSCs) are now widely believed to come from their paracrine signalling, i.e. secreted factors such as cytokines, chemokines, and extracellular vesicles (EVs). Cell-free therapy using EVs is an active and emerging field in regenerative medicine. Typical 2D cultures on tissue culture plastic is far removed from the physiological environment of MSCs. The application of 3D cell culture allows MSCs to adapt to their cellular niche environment which, in turn, influences their paracrine signalling activity. In this study we evaluated the impact of 3D MSCs culture on EVs secretion, cargo proteome composition, and functional assessment in immunomodulatory, anti-inflammatory and anti-fibrotic properties. MSC-EVs from 2D and 3D cultures expressed classical EV markers CD81, CD63, and CD9 with particle diameter of <100nm. There were distinct changes in immunomodulatory potencies where 3D MSC-EVs increased IL-2 production and significantly reduced macrophage phagocytosis. Administration of 2D and 3D EVs following double dose bleomycin challenge in aged mice showed a marked increase of bodyweight loss in 3D group throughout days 7-28. Histopathological observations of lung tissues in 3D group showed increased collagen deposition, myofibroblast differentiation and leukocytes infiltrations. Assessment of lung mechanics showed 3D group did not improve lung function and instead exhibited increased resistance and tissue damping. Proteome profiling of MSC-EV composition revealed molecular enrichment of EV markers and differential proteome between EVs from 2D and 3D culture condition associated with immune-based and fibrosis/extracellular matrix/membrane organization associated function. This study provides insight into distinct variation in EV protein composition dependent on the cellular microenvironment of the parental cells, which could have implications in their therapeutic effect and potency. Overall, this work suggests that EVs produced from 3D MSC cultures did not synergistically enhance typical MSC-EV properties expected from 2D cultures (immunomodulation, anti-fibrotic, anti-inflammatory). The outcome highlights critical differences between MSC-EVs obtained from different culture microenvironments, which should be considered when scaling up MSC culture for clinical manufacturing.